Restitution, chaos and quest: experiences of families with children diagnosed with cerebral palsy - Asante, Emmanuel (2020)
Background: Cerebral palsy (CP) is considered a major physical disability among the childhood developmental disabilities, affecting the functional development of children (Jones et al., 2007), with a prevalence of 2 to 2.5 per 1000 live births (Dolk et al., 2006, Hutton and Pharoah, 2006). Existing research is dominated by the voice of the mother with the voices of other significant family members rarely reported. Incorporation of the voices of other family members is important for a holistic understanding of the experience of living with a child with cerebral palsy. This is particularly true in developing settings, like Ghana, where it is common for both the nuclear and the extended family to live together.